Coercive solvability conditions of an infinite system of difference equations with complex coefficients - Ospanov, K.N.; Bekjan, T.N.; Beisenova, D.R. (Bulletin of the Karaganda University. Mathematics Series, 2017)
These estimates completely describe definition range of the matrix operator which corresponds to system. Coefficients of system make the unlimited sequences. And the received results do not depend on fluctuation of these coefficients. The last fact shows that the nature of infinitely difference systems absolutely other than singular differential equations.